Morphologic Radiographic Study of the Proximal Sesamoid Bones of the Forelimb in Thoroughbred Racehorses in Training. (25th June 2013) - Beccati, F.; Gialletti, R.; Giontella, A.; Davanzo, S.; Di Meo, A.; Pepe, M.
Summary The aim of this study was to identify differences in bone shape (height and width) of proximal sesamoid bones (PSB) in 2‐year‐old Thoroughbred racehorses in training. Dorsal 15° proximal‐palmarodistal oblique images of each metacarpophalangeal joint were acquired before the horses started training and at 1 year after the start of exercise and racing. There were no changes in height and width of PSBs induced by training. There was a significant difference of height and width between medial and lateral PSBs. In both forelimbs, the medial PSB was significantly wider and shorter than the lateral PSB. The medial PSB of the right forelimb was significantly wider than that of the left forelimb. These results might explain some limb predilection for fracture of PSBs. The difference in strain pattern between medial and lateral PSBs in different loading conditions needs to be investigated.